Treatment of Hepatitis C Virus Infection in Kidney Transplant Recipients: Case Report - Caeiro, F (2012)
Chronic hepatitis C virus (HCV) infection exists in a large proportion of patients undergoing renal transplantation. Nowadays it is not considered to be an absolute contraindication to transplantation; however, it is associated with an increased risk for the patient and accounts for a shorter half-life of the renal allograft. We present three transplant recipients who displayed serious hepatic dysfunction after renal transplantation due to an HCV infection. In two of these cases, the liver biopsies established the diagnosis of FCH. In the third case, the liver biopsy was compatible with the early stages of FCH. All patients were started on peg-interferon alfa 2-b and ribavirin with subsequent normalization of hepatic function and early complete viral responses.